Mammographic Density and Estrogen Receptor α Gene Polymorphism in Javanese Women - Lina Choridah; Teguh Aryandono; Arif Faisal; Ahmad Hamim Sadewa; Dewajani Purnomosari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Estrogen plays important roles in breast cancer as it binds its receptor in breast tissue. The most studied variants in estrogen receptor α encoded by ESR1 gene are the ESR1 PvuII and XbaI polymorphisms, which were associated with lower sensitivity to estrogen. We determined the proportion of ESR1 XbaI and PvuII polymorphisms in Javanese woman in Yogyakarta, Indonesia and analyzed the correlation between genetic variations with mammogram density. ESR1 XbaI and PvuII polymorphisms of 50 cases and 58 controls were identified using PCR-RFLP. Breast density was assessed based on digitizer mammograms. Quantitative analysis was performed using an interactive program based on cumulus of two thresholds. Mean of density and frequencies of SNPs were compared between cases and controls to identify the association between SNPs and cancer susceptibility. Mammographic density was significantly higher in cases (52%) than controls (0.41%) (p < 0.05). Women with one or two copies of the PvuII T allele and XbaI A allele had higher mammographic density compared with women with C and G alleles, respectively. The proportion between PP and TT genotype was not statistically significant (p > 0.05), while the proportion between AA and GG was significantly different (p < 0.05). Haplotype 2 (CG/PX) was associated with lower sensitivity to estrogen and reflects a decrease of mammographic density. These findings were consistent with other studies that showed that ESR1 polymorphisms may affect breast cancer risk through differences in breast density.